A Cross-Sectional Study Examining the Role of Climate Variability in Shaping Trypanosomiasis Trends in Binga District, Zimbabwe (2008-2023): A Multi-Method Survey - Nozithelo Ndiweni MSc; Perez Livias Moyo MSc; Wilfred Njabulo Nunu PhD; Joyce Tsoka-Gwegweni PhD (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
Climate variability, particularly global warming, is expected to have a significant impact on the interactions between pathogens, vectors, and animal and human hosts. Trypanosomiasis, a neglected zoonotic disease, is particularly sensitive to changes in climate, as increased temperatures can accelerate vector development and expand geographical range. This disease remains prevalent in Zimbabwe, with the Binga District being disproportionately affected. This study aimed to explore the effects of climate variability on the epidemiology of trypanosomiasis in the Binga District of Zimbabwe from 2008 to 2023. A multi-method approach was used to incorporate secondary data sources and a data-collection guide. Data collection involved a checklist and questionnaire administered using the Kobo Collect Toolbox. Bivariate correlations were employed to investigate the association between climate variability and trypanosomiasis occurrence. Rainfall and temperature data are presented as line graphs and maps at 3-year intervals for the period 2008 to 2023. Spatial analysis was conducted by overlaying climate data with the reported suspected cases of trypanosomiasis. The findings revealed a notable increase in annual case reports, correlating with increasing maximum and fluctuating average temperatures. Specifically, higher annual average temperatures were recorded in 2008 and 2017, coinciding with an increased incidence of trypanosomiasis. These findings underscore the critical role of climate variability in shaping trypanosomiasis trends in the Binga District of Zimbabwe. These findings highlight the importance of effective disease control strategies in response to climate-induced changes.